THE INFLUENCE OF COMMUNICATION AND SOCIAL WORK ENVIRONMENT ON EMPLOYEES' INTERPERSONAL RELATIONSHIPS - Nadya Rahmadhanti; Aurik Gustomo (UPT Publikasi Ilmiah UNISBA, 2024)
This study explores the influence of communication and the social work environment on employees' interpersonal relationships, focusing on a sample of 60 employees from the Cimahi City Regional Government Agency. The research employs a saturated sampling method, where the entire population is included in the sample, ensuring comprehensive data representation. Data was collected through the distribution of structured questionnaires, designed to assess the quality of communication, the nature of the social work environment, and the resulting interpersonal relationships among employees. To analyze the collected data, multiple linear regression, t-tests, and f-tests were applied, allowing for both simultaneous and individual assessment of the variables in question. The findings reveal that both communication and the social work environment have a significant combined impact on the quality of interpersonal relationships among employees. Furthermore, the study indicates that when analyzed separately, both communication and the social work environment independently contribute to the development and maintenance of interpersonal relationships within the workplace. These results underscore the importance of fostering effective communication and a supportive social work environment to enhance workplace relationships, which are crucial for organizational success and employee well-being.